Increased risk of hospital-acquired foot ulcers in people with diabetes: large prospective study and implications for practice. Issue 1 (9th July 2018) - Wensley, Frances; Kerry, Christopher; Rayman, Gerry
Abstract : Aims: Diabetes increases the risk of costly and potentially preventable hospital-acquired pressure ulceration. Given that peripheral arterial disease and neuropathy, important risk factors for foot ulceration, are more common in people with diabetes, their risk of hospital-acquired foot ulceration (HAFU) in particular may be even greater. This study aims to determine this risk. Methods: Using data collected over 2 years from all admissions to the Ipswich Hospital NHS Trust, we conducted a prospective multilevel regression analysis of the risk of HAFU in 5043 admissions of people with diabetes versus 23 599 without diabetes. Patients over 50 years who developed HAFU at least 48 hours after admission were included in analyses. Progressive adjustment for important risk factors and subgroup analyses were conducted to compare patients with and without diabetes. Results: There were significant differences between patients with and without diabetes among a range of covariates including sex, Comorbidity Score, and length of stay (p value <0.001). After progressive adjustment for age, sex, and other risk factors, there persisted a significant increase risk of HAFU in people with diabetes (OR 2.24; 95% CI 1.80 to 2.69). There were no substantial differences between clinically relevant subgroups. Conclusions: These analyses demonstrate at least a twofold increase in the risk of HAFU in patients with diabetes and suggest further work should focus on specific processes to detect those inpatients with diabetes at increased risk, in whom preventative measures may reduce the prevalence of this costly complication.